Matra basti a boon to geriatric population-A conceptual review. - Thakar, Aastha; Patil, Ashok (International Research Journal of Ayurveda & Yoga, 2026)
According to Ayurveda, vata dosha is the dosha that predominates in old age and that vitiation of vata is the primary cause of the majority of illnesses in the elderly. Due to its broader therapeutic actions, Matra Basti treatment also acts as a rejuvenative, curative, and preventive therapy to improve the quality of life of the geriatric population. Matra Basti treatment balances particular doshas, which makes it more effective in managing a range of geriatric disorders.The progressive deterioration of multisystem function at the cellular level is linked to the physiological phenomenon of aging. Owing to degenerative changes, musculoskeletal and neurological illnesses are the most prevalent conditions among the elderly population. This article here portrays the importance of Matra Basti in Geriatric care.